2019
DOI: 10.1055/s-0039-1693031
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Marker in Patients Undergoing Spinal Surgery: Prognostic Nutritional Index

Abstract: Objective The relationship of a preoperative Prognostic Nutritional Index (PNI) with perioperative adverse events (PAEs) other than delirium has never been described in patients undergoing spinal surgery. We aimed to evaluate the impact of admission PNI on the outcome of patients undergoing spinal surgery. Methods Medical records of 408 consecutive patients 50 years or older undergoing spinal surgery were reviewed. Patients' information including demographic data, routine preoperative laboratory test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…Of those, 17 of patients were female, and 19 were male (p>0,05). As stated in the literature, the expected mortality ranges from 1,11 to 8,78 (17). In Turkey, a recent study performed by Polat et al, the 30-day mortality rate was 2.7% (n=17) 25 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Of those, 17 of patients were female, and 19 were male (p>0,05). As stated in the literature, the expected mortality ranges from 1,11 to 8,78 (17). In Turkey, a recent study performed by Polat et al, the 30-day mortality rate was 2.7% (n=17) 25 .…”
Section: Discussionmentioning
confidence: 91%
“…Although the controversy over the insufficiency or superiority of off/on-pump CABG continues, it accounts for 15-30% of all CABG cases that vary in different national authorities. In Turkey, private hospital surgeons perform new surgical techniques in major experience and publish articles with great outcomes 17 . In our study, we reported one of the critical parts of the CABG surgery in the south region of Turkey, as covering with a primary capacity private-run cardiovascular surgery hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Immune-nutritional status are di cult to show from physical examination and imaging examinations, but biochemical indicators in blood tests may change in the acute phase of tSCI. PNI and COUNT scores are Immune-nutritional screening tools composed of different immune and nutritional biochemical indicators which have been widely used to predict the prognosis of patients with severe traumatic brain injury, cancer or spinal surgery 4,5,17 .PNI is calculated from albumin, lymphocytes, while COUNT score is calculated from albumin, lymphocytes, total cholesterol. Albumin is often considered a nutritional marker, but it may also exert neuroprotective effects by reducing cerebral edema and improving the metabolic activity of neurons 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This level-II, prospective, comparative study included civilians injured in the Syrian Civil War 2015 and 2017. All patients acknowledged and signed the informed patient consent form for the study after the completion of demographic data collection [17]. We obtained study approval from the institute where the study was conducted (Number: 2018–255-0002).…”
Section: Methodsmentioning
confidence: 99%